Fishing motivations and preferences of recreational anglers at pay-fishing ponds in Serdang, Selangor - Mohammad Saidi, Mohammad Nazrin; Kamaruddin, Izharuddin Shah (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
This study was conducted to understand the basic socio-demographic backgrounds and fishing motivations of anglers who fish at three pay-fishing ponds in Serdang, Selangor. This study also try to understand the angler’s preferences towards the non-native fish species. A set of survey questionnaire was used to collect anglers data with a face-to-face sampling technique. A total of 100 pay-fishing pond anglers were surveyed (62.5% of response rate). Seventy-four percent of the anglers are Malay, followed by Chinese (20.0%) and Indian anglers (6.0%). The highest group was represented by the age group of 30 to 39 years old (46.7%). Most of the anglers are self-employed (38.0%), have a certificate or Diploma (44.0%), and married (75.0%). In average, the anglers have 14.03±1.18 years (mean±S.E.) of fishing experience, and 7.39±0.70 years of fishing experience specifically at pay-fishing pond. The results of this study revealed that the highest fishing motivation placed by the anglers was ‘avoiding a moment from stress at work’ (4.49±0.05, from a Likert scale of 1 to 5) while the lowest motivation was ‘failed to catch a fish’ (1.78±0.12). Later, the fishing motivations could be categorized into four different groups, which related to the fishery resources, psychological, social and skill. The fishing motivations were found to be difference between different basic socio-demographic background groups of anglers. Meanwhile, in terms of the angler’s preferences towards the non-native species, most of the anglers preferred to catch patin (4.26±0.08) and baung (4.21±0.08), and they are less likely to catch keli (3.83±0.11). The findings of this research could provide some basic information about the pay-fishing pond anglers in Serdang, and could be used as a basis for the managers to better manage recreational fishing activity at pay-fishing ponds in Malaysia.